Copper-free NaO material

By accurately controlling the proportion of raw materials and multi-step fine processing technology, high-performance copper-free NaO materials were prepared, which solved the problems of poor thermal conductivity, low service life and insufficient wear resistance of existing materials in high temperature environments, and achieved high performance and environmental protection of the materials.

CN119684972APending Publication Date: 2025-03-25JIANGSU FANGXING FRICTION MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411992821.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing copper-free NaO friction materials have poor thermal conductivity, low service life and insufficient wear resistance in high-temperature environments, which limits their application in high-performance braking systems.

Method used

By precisely controlling the proportion of raw materials, a multi-step fine processing process is adopted, including melting, ball milling, sonication and cold isostatic molding, high-performance copper-free NaO materials are prepared. This process not only improves the uniformity and density of the material, but also reduces residual stress inside the material and improves surface quality through post-treatment steps such as oil quenching and ultrasonic cleaning.

Benefits of technology

It realizes the high performance of copper-free NaO materials, improves its stability and wear resistance in high-temperature environments, broadens its application range in high-performance braking systems, and avoids heavy metal pollution to the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119684972A_ABST
    Figure CN119684972A_ABST
Patent Text Reader

Abstract

The invention provides a copper-free NaO material. The copper-free NaO material is prepared from the following raw materials in parts by weight: 42.2 to 43.0 parts of sodium oxide, 2.0 to 3.0 parts of aluminum oxide, 4.0 to 6.0 parts of silicon oxide, 6.4 to 7.0 parts of calcium oxide, 4.0 to 6.0 parts of magnesium oxide, 8.6 to 9.0 parts of iron oxide, 4.8 to 5.2 parts of zinc oxide, 4.0 to 5.0 parts of titanium oxide, 4.0 to 6.0 parts of boride, 4.0 to 5.0 parts of barium oxide and 12.3 to 13.0 parts of water. High uniformity and compactness of the material can be achieved, the residual stress in the material is reduced, the surface quality is improved, the performance of the material is improved, and the application range of the material is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and more specifically, to a copper-free NaO material. Background Art

[0002] With the development of modern transportation towards high speed and heavy load, and the increasing awareness of people on health and environmental protection, the requirements for friction materials are getting higher and higher. Early friction materials mostly used asbestos as a reinforcing material, but the harm of asbestos to the environment and human health has been widely recognized, so it has been gradually eliminated. Subsequently, semi-metallic and low-metallic friction materials reinforced with steel wool appeared. Although they solved the problems of high speed and heavy load, they had disadvantages such as heavy weight, high hardness, and easy rust. Therefore, the development of NAO friction materials without asbestos and steel wool has become a new development direction. However, these materials have problems such as poor thermal conductivity and low life in practical applications, especially in copper-free NAO friction materials.

[0003] In the process of implementing the embodiments of the present invention, the inventors found that there are at least the following problems or defects in the prior art: the copper-free NAO friction material lacks metal materials with high thermal conductivity, which leads to excessively high friction interface temperature and more serious thermal decay phenomenon. At the same time, the wear resistance of these materials is also poor, which limits their application in high-performance braking systems. Summary of the invention

[0004] The invention provides a copper-free NaO material.

[0005] In a first aspect of the present invention, a copper-free NaO material is provided, which is made of the following raw materials in parts by weight: 42.2-43.0 parts of sodium oxide, 2.0-3.0 parts of aluminum oxide, 4.0-6.0 parts of silicon oxide, 6.4-7.0 parts of calcium oxide, 4.0-6.0 parts of magnesium oxide, 8.6-9.0 parts of iron oxide, 4.8-5.2 parts of zinc oxide, 4.0-5.0 parts of titanium oxide, 4.0-6.0 parts of boride, 4.0-5.0 parts of barium oxide and 12.3-13.0 parts of water.

[0006] Furthermore, the copper-free NaO material is made of the following raw materials in parts by weight: 42.2 parts of sodium oxide, 2.0 parts of aluminum oxide, 4.0 parts of silicon oxide, 6.4 parts of calcium oxide, 4.0 parts of magnesium oxide, 8.6 parts of iron oxide, 4.8 parts of zinc oxide, 4.0 parts of titanium oxide, 6.0 parts of boride, 4.0 parts of barium oxide and 12.3 parts of water.

[0007] Furthermore, the copper-free NaO material is made of the following raw materials in parts by weight: 43.0 parts of sodium oxide, 3.0 parts of aluminum oxide, 5.0 parts of silicon oxide, 7.0 parts of calcium oxide, 6.0 parts of magnesium oxide, 9.0 parts of iron oxide, 5.2 parts of zinc oxide, 5.0 parts of titanium oxide, 6.0 parts of boride, 5.0 parts of barium oxide and 13.0 parts of water.

[0008] Furthermore, the copper-free NaO material is made of the following raw materials in parts by weight: 42.8 parts of sodium oxide, 2.6 parts of aluminum oxide, 5.2 parts of silicon oxide, 6.8 parts of calcium oxide, 5.1 parts of magnesium oxide, 8.8 parts of iron oxide, 5.0 parts of zinc oxide, 4.5 parts of titanium oxide, 4.5 parts of boride, 4.5 parts of barium oxide and 13.0 parts of water.

[0009] Furthermore, the boride is a combination of one or more of borates, borax, boric acid, borosilicate, calcium borate, and magnesium borate.

[0010] Furthermore, the boride is a mixture of borate, borax and boric acid, and the weights of the borate, borax and boric acid are equal.

[0011] Furthermore, the boride is borosilicate, and in parts by weight, the silicon oxide comprises 4.0 parts and the boride comprises 6.0 parts.

[0012] Furthermore, the boride is calcium borate, and the purity of the calcium borate is greater than 99.5%.

[0013] In a second aspect of the present invention, a method for preparing a copper-free NaO material is provided, comprising the following steps: S1. The aluminum oxide and silicon oxide are melted at 1500°C to 1600°C in a protective atmosphere for at least 2 hours to form a uniform melt, and then naturally cooled to 800°C to 900°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for at least 48 hours, and the mass ratio of the ball-milling medium to the powder was 10:1. After the ball-milling, the powder was screened through a 200-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 is mixed with the powder obtained in step S2, deionized water is added, and the mixture is stirred at a speed of 1500 rpm for at least 2 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry is kept in a water bath at 50°C to 60°C, and ultrasonically treated using an ultrasonic processor with a processing power of 100W to 200W for at least 30 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry is subjected to cold isostatic pressing at a pressure of 5 to 10 atmospheres for 1 to 2 hours to form a dense green body; S6. The green body is sintered at 1100°C to 1200°C under nitrogen protection for 4 to 6 hours, and the green body is turned over every 30 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 150°C to 200°C for 5 to 10 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 10 to 20 minutes to remove the grinding and polishing materials remaining on the surface, and then dried and packaged for later use.

[0014] Further, in step S2, the particle size of the powder is less than 400 mesh, and the powder is subjected to the following additional treatments: a. Refinement treatment by ball mill to ensure the uniformity and reactivity of powder; b. Heat treatment in an inert gas atmosphere to remove adsorbed water and organic impurities on the powder surface; c. Screening by sieving machine to ensure the consistency and precise control of powder particle size; d. Add an appropriate amount of surfactant to the powder to improve the dispersibility of the powder and prevent agglomeration; e. Dry the treated powder in a drying oven until the moisture content is less than 0.5% to ensure the stability of the material and prevent hydrolysis.

[0015] According to the above-mentioned embodiments of the present invention, at least the following beneficial effects are achieved: the preparation method of copper-free NaO material can improve the uniformity and density of the material by precisely controlling the raw material ratio and adopting a multi-step fine processing process. The method includes steps such as melting, ball milling, ultrasonic treatment and cold isostatic pressing, which cooperate with each other to ensure the high performance of the material. At the same time, through post-processing steps such as oil quenching and ultrasonic cleaning, the residual stress inside the material can be reduced and the surface quality can be improved. These processing methods can not only improve the mechanical properties and wear resistance of the material, but also enhance its stability in high temperature environments, thereby broadening the application range of the material.

[0016] In addition, the copper-free NaO material of the present invention does not contain heavy metal elements such as copper, so it can avoid heavy metal pollution to the environment during the friction process. This environmentally friendly friction material can meet the increasingly stringent environmental regulations, and due to its excellent physical and chemical properties, it can provide a safer and more reliable braking solution without affecting the braking performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and other objects, features and advantages of the exemplary embodiments of the present invention will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present invention are shown in an exemplary and non-limiting manner, in which: Figure 1 A schematic flow chart of a method for preparing a copper-free NaO material provided in one embodiment of the present invention. DETAILED DESCRIPTION

[0018] The principles and spirit of the present invention will be described below with reference to several exemplary embodiments. It should be understood that these embodiments are provided only to enable those skilled in the art to better understand and implement the present invention, and are not intended to limit the scope of the present invention in any way. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0019] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. All features disclosed in this specification, or steps in all methods or processes disclosed, except for mutually exclusive characteristics and / or steps, can be combined in any way, unless otherwise described, and can be replaced by other equivalent or alternative features with similar purposes, that is, unless otherwise described, each feature is only one embodiment in a series of equivalent or similar features. Example 1

[0020] A method for preparing a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 42.2 parts of sodium oxide, 2.0 parts of aluminum oxide, 4.0 parts of silicon oxide, 6.4 parts of calcium oxide, 4.0 parts of magnesium oxide, 8.6 parts of iron oxide, 4.8 parts of zinc oxide, 4.0 parts of titanium oxide, 4.0 parts of boride, 4.0 parts of barium oxide and 12.3 parts of water. The preparation method of this embodiment includes the following steps: S1. The aluminum oxide and silicon oxide are melted at 1500°C to 1600°C in a protective atmosphere for at least 2 hours to form a uniform melt, and then naturally cooled to 800°C to 900°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for at least 48 hours, and the mass ratio of the ball-milling medium to the powder was 10:1. After the ball-milling, the powder was screened through a 200-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 is mixed with the powder obtained in step S2, deionized water is added, and the mixture is stirred at a speed of 1500 rpm for at least 2 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry is kept in a water bath at 50°C to 60°C, and ultrasonically treated using an ultrasonic processor with a processing power of 100W to 200W for at least 30 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry is subjected to cold isostatic pressing at a pressure of 5 to 10 atmospheres for 1 to 2 hours to form a dense green body; S6. The green body is sintered at 1100°C to 1200°C under nitrogen protection for 4 to 6 hours, and the green body is turned over every 30 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 150°C to 200°C for 5 to 10 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 10 to 20 minutes to remove the grinding and polishing materials remaining on the surface, and then dried and packaged for later use.

[0021] In this embodiment, the boride is selected as borate, and the purity of the borate is greater than 99.5% to ensure the high performance and environmental friendliness of the copper-free NaO material. Experimental data show that the copper-free NaO material prepared according to the above steps S1 to S9 has excellent mechanical properties and wear resistance, does not contain heavy metals, and is environmentally friendly.

[0022] Experimental data: Synthesis method: Follow the above steps S1 to S9.

[0023] Reaction conditions: melting temperature 1500°C to 1600°C, melting time not less than 2 hours, ball milling time not less than 48 hours, ultrasonic treatment power 100W to 200W, cold isostatic pressing pressure 5 to 10 atmospheres, sintering temperature 1100°C to 1200°C, oil quenching temperature 150°C to 200°C, ultrasonic cleaning time 10 to 20 minutes.

[0024] Yield: The theoretical yield is 100%, and the actual yield exceeds 95%.

[0025] Purity: Through X-ray diffraction (XRD) analysis, the phase purity of copper-free NaO material reaches more than 99%.

[0026] Application and Effect: The copper-free NaO material is suitable for manufacturing high-performance friction materials, such as brake linings, etc. Experiments show that the copper-free NaO material prepared by this embodiment has excellent high-temperature stability and low wear rate, does not contain heavy metals such as copper, and is environmentally friendly. Example 2

[0027] A method for preparing a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 42.2 parts of sodium oxide, 2.0 parts of aluminum oxide, 4.0 parts of silicon oxide, 6.4 parts of calcium oxide, 4.0 parts of magnesium oxide, 8.6 parts of iron oxide, 4.8 parts of zinc oxide, 4.0 parts of titanium oxide, 6.0 parts of boride, 4.0 parts of barium oxide and 12.3 parts of water. The preparation method of this embodiment includes the following steps: S1. The aluminum oxide and silicon oxide are melted at 1550°C in a protective atmosphere for 3 hours to form a uniform melt, and then naturally cooled to 850°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for 72 hours, and the mass ratio of the ball-milling medium to the powder was 10:1. After the ball-milling, the powder was screened through a 200-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 was mixed with the powder obtained in step S2, deionized water was added, and the mixture was stirred at 1500 rpm for 3 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry was kept warm in a water bath at 55°C and ultrasonically treated with an ultrasonic processor at a power of 150 W for 45 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry was subjected to cold isostatic pressing at 8 atmospheres for 1.5 hours to form a dense green body; S6. The green body was sintered at 1150°C under nitrogen protection for 5 hours, and the green body was turned over every 30 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 175°C for 7 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 15 minutes to remove the residual ground and polished materials on the surface, and then dried and packaged for later use.

[0028] In this embodiment, the boride is selected as borate, and the purity of the borate is greater than 99.5%, ensuring the high performance and environmental friendliness of the copper-free NaO material. Experimental data show that the copper-free NaO material prepared according to the above steps S1 to S9 has excellent mechanical properties and wear resistance, does not contain heavy metals, and is environmentally friendly.

[0029] Experimental data: Synthesis method: Follow the above steps S1 to S9.

[0030] Reaction conditions: melting temperature 1550°C, melting time 3 hours, ball milling time 72 hours, ultrasonic treatment power 150W, cold isostatic pressing pressure 8 atmospheres, sintering temperature 1150°C, oil quenching temperature 175°C, ultrasonic cleaning time 15 minutes.

[0031] Yield: The theoretical yield is 100%, and the actual yield exceeds 95%.

[0032] Purity: Through X-ray diffraction (XRD) analysis, the phase purity of copper-free NaO material reaches more than 99%.

[0033] Application and Effect: The copper-free NaO material is suitable for manufacturing high-performance friction materials, such as brake linings, etc. Experiments show that the copper-free NaO material prepared by this embodiment has excellent high-temperature stability and low wear rate, does not contain heavy metals such as copper, and is environmentally friendly. Example 3

[0034] A method for preparing a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 43.0 parts of sodium oxide, 3.0 parts of aluminum oxide, 5.0 parts of silicon oxide, 7.0 parts of calcium oxide, 6.0 parts of magnesium oxide, 9.0 parts of iron oxide, 5.2 parts of zinc oxide, 5.0 parts of titanium oxide, 6.0 parts of boride, 5.0 parts of barium oxide and 13.0 parts of water. The preparation method of this embodiment includes the following steps: S1. The aluminum oxide and silicon oxide are melted at 1580°C in a protective atmosphere for 4 hours to form a uniform melt, and then naturally cooled to 830°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball milled in a ball mill with ethanol as the medium for 96 hours, the mass ratio of the ball milling medium to the powder was 15:1, and after the ball milling, they were screened through a 325 mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 was mixed with the powder obtained in step S2, deionized water was added, and the mixture was stirred at a speed of 1800 rpm for 4 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry was kept warm in a water bath at 58°C and ultrasonically treated with an ultrasonic processor at a power of 180 W for 60 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry was subjected to cold isostatic pressing at 10 atmospheres for 2 hours to form a dense green body; S6. The green body was sintered at 1180°C under nitrogen protection for 6 hours, and the green body was turned over every 20 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 165°C for 8 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 18 minutes to remove the residual ground and polished materials on the surface, and then dried and packaged for later use.

[0035] In this embodiment, the boride is selected as calcium borate, and the purity of calcium borate is greater than 99.8% to ensure the high performance and environmental friendliness of the copper-free NaO material. Experimental data show that the copper-free NaO material prepared according to the above steps S1 to S9 has excellent mechanical properties and wear resistance, does not contain heavy metals, and is environmentally friendly.

[0036] Experimental data: Synthesis method: Follow the above steps S1 to S9.

[0037] Reaction conditions: melting temperature 1580°C, melting time 4 hours, ball milling time 96 hours, ultrasonic treatment power 180W, cold isostatic pressing pressure 10 atmospheres, sintering temperature 1180°C, oil quenching temperature 165°C, ultrasonic cleaning time 18 minutes.

[0038] Yield: The theoretical yield is 100%, and the actual yield exceeds 96%.

[0039] Purity: Through X-ray diffraction (XRD) analysis, the phase purity of copper-free NaO material reaches more than 99%.

[0040] Application and Effect: The copper-free NaO material is suitable for manufacturing high-performance friction materials, such as brake linings, etc. Experiments show that the copper-free NaO material prepared by this embodiment has excellent high-temperature stability and low wear rate, does not contain heavy metals such as copper, and is environmentally friendly. Example 4

[0041] A method for preparing a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 42.8 parts of sodium oxide, 2.6 parts of aluminum oxide, 5.2 parts of silicon oxide, 6.8 parts of calcium oxide, 5.1 parts of magnesium oxide, 8.8 parts of iron oxide, 5.0 parts of zinc oxide, 4.5 parts of titanium oxide, 4.5 parts of boride, 4.5 parts of barium oxide and 13.0 parts of water. The preparation method of this embodiment includes the following steps: S1. The aluminum oxide and silicon oxide are melted at 1590°C in a protective atmosphere for 3.5 hours to form a uniform melt, and then naturally cooled to 840°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for 80 hours, the mass ratio of the ball-milling medium to the powder was 12:1, and after the ball-milling, the powder was screened through a 325-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 is mixed with the powder obtained in step S2, deionized water is added, and the mixture is stirred at 1650 rpm for 3.5 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry was kept warm in a water bath at 55°C and ultrasonically treated with an ultrasonic processor at a power of 160 W for 50 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry was subjected to cold isostatic pressing at 8.5 atmospheres for 1.8 hours to form a dense green body; S6. The green body was sintered at 1190°C under nitrogen protection for 5.5 hours, and the green body was turned over every 25 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 160° C. for 7.5 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 16 minutes to remove the residual ground and polished materials on the surface, and then dried and packaged for later use.

[0042] In this embodiment, the boride is selected as a mixture of borate and borax, and the weight of borate and borax is equal to ensure the high performance and environmental friendliness of the copper-free NaO material. Experimental data show that the copper-free NaO material prepared according to the above steps S1 to S9 has excellent mechanical properties and wear resistance, does not contain heavy metals, and is environmentally friendly.

[0043] Experimental data: Synthesis method: Follow the above steps S1 to S9.

[0044] Reaction conditions: melting temperature 1590°C, melting time 3.5 hours, ball milling time 80 hours, ultrasonic treatment power 160W, cold isostatic pressing pressure 8.5 atmospheres, sintering temperature 1190°C, oil quenching temperature 160°C, ultrasonic cleaning time 16 minutes.

[0045] Yield: The theoretical yield is 100%, and the actual yield exceeds 96%.

[0046] Purity: Through X-ray diffraction (XRD) analysis, the phase purity of copper-free NaO material reaches more than 99%.

[0047] Application and Effect: The copper-free NaO material is suitable for manufacturing high-performance friction materials, such as brake linings, etc. Experiments show that the copper-free NaO material prepared by this embodiment has excellent high-temperature stability and low wear rate, does not contain heavy metals such as copper, and is environmentally friendly.

[0048] Embodiment 5: A method for preparing a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 42.2 parts of sodium oxide, 2.0 parts of aluminum oxide, 4.0 parts of silicon oxide, 6.4 parts of calcium oxide, 4.0 parts of magnesium oxide, 8.6 parts of iron oxide, 4.8 parts of zinc oxide, 4.0 parts of titanium oxide, 6.0 parts of boride, 4.0 parts of barium oxide and 12.3 parts of water. The preparation method of this embodiment includes the following steps: S1. The aluminum oxide and silicon oxide are melted at 1600°C in a protective atmosphere for 2.5 hours to form a uniform melt, and then naturally cooled to 850°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for 48.5 hours, the mass ratio of the ball-milling medium to the powder was 10:1, and after the ball-milling, the powder was screened through a 250-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 was mixed with the powder obtained in step S2, deionized water was added, and the mixture was stirred at 1500 rpm for 2.5 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry was kept warm in a water bath at 55°C and ultrasonically treated with an ultrasonic processor at a power of 150 W for 35 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry was subjected to cold isostatic pressing at 7 atmospheres for 1.75 hours to form a dense green body; S6. The green body was sintered at 1150°C under nitrogen protection for 5 hours, and the green body was turned over every 30 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 155°C for 7 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 15 minutes to remove the residual ground and polished materials on the surface, and then dried and packaged for later use.

[0049] In this embodiment, the boride is selected as a mixture of borate, borax and boric acid, wherein the weights of borate, borax and boric acid are equal to ensure the high performance and environmental friendliness of the copper-free NaO material. Experimental data show that the copper-free NaO material prepared according to the above steps S1 to S9 has excellent mechanical properties and wear resistance, does not contain heavy metals, and is environmentally friendly.

[0050] Experimental data: Synthesis method: Follow the above steps S1 to S9.

[0051] Reaction conditions: melting temperature 1600°C, melting time 2.5 hours, ball milling time 48.5 hours, ultrasonic treatment power 150W, cold isostatic pressing pressure 7 atmospheres, sintering temperature 1150°C, oil quenching temperature 155°C, ultrasonic cleaning time 15 minutes.

[0052] Yield: The theoretical yield is 100%, and the actual yield exceeds 95%.

[0053] Purity: Through X-ray diffraction (XRD) analysis, the phase purity of copper-free NaO material reaches more than 99%.

[0054] Application and Effect: The copper-free NaO material is suitable for manufacturing high-performance friction materials, such as brake linings, etc. Experiments show that the copper-free NaO material prepared by this embodiment has excellent high-temperature stability and low wear rate, does not contain heavy metals such as copper, and is environmentally friendly.

[0055] Embodiment 6: A method for preparing a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 43.0 parts of sodium oxide, 3.0 parts of aluminum oxide, 5.0 parts of silicon oxide, 7.0 parts of calcium oxide, 6.0 parts of magnesium oxide, 9.0 parts of iron oxide, 5.2 parts of zinc oxide, 5.0 parts of titanium oxide, 6.0 parts of boride, 5.0 parts of barium oxide and 13.0 parts of water. The preparation method of this embodiment includes the following steps: S1. The aluminum oxide and silicon oxide are melted at 1590°C in a protective atmosphere for 3 hours to form a uniform melt, and then naturally cooled to 870°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for 48 hours, and the mass ratio of the ball-milling medium to the powder was 10:1. After the ball-milling, the powder was screened through a 325-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 was mixed with the powder obtained in step S2, deionized water was added, and the mixture was stirred at 1600 rpm for 3 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry was kept warm in a water bath at 58°C and ultrasonically treated with an ultrasonic processor at a power of 180 W for 40 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry was subjected to cold isostatic pressing at 9 atmospheres for 2 hours to form a dense green body; S6. The green body was sintered at 1180°C under nitrogen protection for 5.5 hours, and the green body was turned over every 30 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 165°C for 9 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 18 minutes to remove the residual ground and polished materials on the surface, and then dried and packaged for later use.

[0056] In this embodiment, the boride is selected as borosilicate, and the weight of silicon oxide is 4.0 parts, and the weight of boride is 6.0 parts, so as to ensure the high performance and environmental friendliness of the copper-free NaO material. Experimental data show that the copper-free NaO material prepared according to the above steps S1 to S9 has excellent mechanical properties and wear resistance, does not contain heavy metals, and is environmentally friendly.

[0057] Experimental data: Synthesis method: Follow the above steps S1 to S9.

[0058] Reaction conditions: melting temperature 1590°C, melting time 3 hours, ball milling time 48 hours, ultrasonic treatment power 180W, cold isostatic pressing pressure 9 atmospheres, sintering temperature 1180°C, oil quenching temperature 165°C, ultrasonic cleaning time 18 minutes.

[0059] Yield: The theoretical yield is 100%, and the actual yield exceeds 96%.

[0060] Purity: Through X-ray diffraction (XRD) analysis, the phase purity of copper-free NaO material reaches more than 99%.

[0061] Application and Effect: The copper-free NaO material is suitable for manufacturing high-performance friction materials, such as brake linings, etc. Experiments show that the copper-free NaO material prepared by this embodiment has excellent high-temperature stability and low wear rate, does not contain heavy metals such as copper, and is environmentally friendly.

[0062] Embodiment 7: A method for preparing a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 42.8 parts of sodium oxide, 2.6 parts of aluminum oxide, 5.2 parts of silicon oxide, 6.8 parts of calcium oxide, 5.1 parts of magnesium oxide, 8.8 parts of iron oxide, 5.0 parts of zinc oxide, 4.5 parts of titanium oxide, 4.5 parts of boride, 4.5 parts of barium oxide and 13.0 parts of water. The preparation method of this embodiment includes the following steps: S1. The aluminum oxide and silicon oxide are melted at 1570°C in a protective atmosphere for 3.2 hours to form a uniform melt, and then naturally cooled to 860°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for 49 hours, and the mass ratio of the ball-milling medium to the powder was 11:1. After the ball-milling, the powder was screened through a 280-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 was mixed with the powder obtained in step S2, deionized water was added, and the mixture was stirred at a speed of 1580 rpm for 3.2 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry was kept warm in a water bath at 56°C and ultrasonically treated with an ultrasonic processor at a power of 165 W for 42 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry was subjected to cold isostatic pressing at 8.8 atmospheres for 1.9 hours to form a dense green body; S6. The green body was sintered at 1170°C under nitrogen protection for 5.3 hours, and the green body was turned over every 28 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 162°C for 8.5 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 17 minutes to remove the residual ground and polished materials on the surface, and then dried and packaged for later use.

[0063] In this embodiment, the boride is selected as calcium borate, and the purity of calcium borate is greater than 99.5% to ensure the high performance and environmental friendliness of the copper-free NaO material. Experimental data show that the copper-free NaO material prepared according to the above steps S1 to S9 has excellent mechanical properties and wear resistance, does not contain heavy metals, and is environmentally friendly.

[0064] Experimental data: Synthesis method: Follow the above steps S1 to S9.

[0065] Reaction conditions: melting temperature 1570°C, melting time 3.2 hours, ball milling time 49 hours, ultrasonic treatment power 165W, cold isostatic pressing pressure 8.8 atmospheres, sintering temperature 1170°C, oil quenching temperature 162°C, ultrasonic cleaning time 17 minutes.

[0066] Yield: The theoretical yield is 100%, and the actual yield exceeds 95.5%.

[0067] Purity: Through X-ray diffraction (XRD) analysis, the phase purity of copper-free NaO material reaches more than 99%.

[0068] Application and Effect: The copper-free NaO material is suitable for manufacturing high-performance friction materials, such as brake linings, etc. Experiments show that the copper-free NaO material prepared by this embodiment has excellent high-temperature stability and low wear rate, does not contain heavy metals such as copper, and is environmentally friendly.

[0069] Embodiment 8: A method for preparing a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 42.8 parts of sodium oxide, 2.6 parts of aluminum oxide, 5.2 parts of silicon oxide, 6.8 parts of calcium oxide, 5.1 parts of magnesium oxide, 8.8 parts of iron oxide, 5.0 parts of zinc oxide, 4.5 parts of titanium oxide, 4.5 parts of boride, 4.5 parts of barium oxide and 13.0 parts of water. The preparation method of this embodiment includes the following steps: S1. The aluminum oxide and silicon oxide are melted at 1580°C in a protective atmosphere for 3 hours to form a uniform melt, and then naturally cooled to 860°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for 48 hours, the mass ratio of the ball-milling medium to the powder was 10:1, and after the ball-milling, the powder was screened through a 250-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 was mixed with the powder obtained in step S2, deionized water was added, and the mixture was stirred at 1500 rpm for 2.5 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry was kept warm in a water bath at 55°C and ultrasonically treated with an ultrasonic processor at a power of 175 W for 45 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry was subjected to cold isostatic pressing at 8.5 atmospheres for 1.75 hours to form a dense green body; S6. The green body was sintered at 1175°C under nitrogen protection for 5.25 hours, and the green body was turned over every 25 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 160° C. for 8 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 16 minutes to remove the residual ground and polished materials on the surface, and then dried and packaged for later use.

[0070] In this embodiment, the boride is selected as calcium borate, and the purity of calcium borate is greater than 99.5% to ensure the high performance and environmental friendliness of the copper-free NaO material. Experimental data show that the copper-free NaO material prepared according to the above steps S1 to S9 has excellent mechanical properties and wear resistance, does not contain heavy metals, and is environmentally friendly.

[0071] Experimental data: Synthesis method: Follow the above steps S1 to S9.

[0072] Reaction conditions: melting temperature 1580°C, melting time 3 hours, ball milling time 48 hours, ultrasonic treatment power 175W, cold isostatic pressing pressure 8.5 atmospheres, sintering temperature 1175°C, oil quenching temperature 160°C, ultrasonic cleaning time 16 minutes.

[0073] Yield: The theoretical yield is 100%, and the actual yield exceeds 95.5%.

[0074] Purity: Through X-ray diffraction (XRD) analysis, the phase purity of copper-free NaO material reaches more than 99%.

[0075] Application and Effect: The copper-free NaO material is suitable for manufacturing high-performance friction materials, such as brake linings, etc. Experiments show that the copper-free NaO material prepared by this embodiment has excellent high-temperature stability and low wear rate, does not contain heavy metals such as copper, and is environmentally friendly.

[0076] Embodiment 9: like Figure 1 As shown, a method for preparing a copper-free NaO material is prepared from the following raw materials in parts by weight: 42.2 parts of sodium oxide, 2.0 parts of aluminum oxide, 4.0 parts of silicon oxide, 6.4 parts of calcium oxide, 4.0 parts of magnesium oxide, 8.6 parts of iron oxide, 4.8 parts of zinc oxide, 4.0 parts of titanium oxide, 6.0 parts of boride, 4.0 parts of barium oxide and 12.3 parts of water. The preparation method of this embodiment includes the following steps: S1. The aluminum oxide and silicon oxide are melted at 1500°C to 1600°C in a protective atmosphere for at least 2 hours to form a uniform melt, and then naturally cooled to 800°C to 900°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for at least 48 hours, and the mass ratio of the ball-milling medium to the powder was 10:1. After the ball-milling, the powder was screened through a 200-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 is mixed with the powder obtained in step S2, deionized water is added, and the mixture is stirred at a speed of 1500 rpm for at least 2 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry is kept in a water bath at 50°C to 60°C, and ultrasonically treated using an ultrasonic processor with a processing power of 100W to 200W for at least 30 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry is subjected to cold isostatic pressing at a pressure of 5 to 10 atmospheres for 1 to 2 hours to form a dense green body; S6. The green body is sintered at 1100°C to 1200°C under nitrogen protection for 4 to 6 hours, and the green body is turned over every 30 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 150°C to 200°C for 5 to 10 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 10 to 20 minutes to remove the grinding and polishing materials remaining on the surface, and then dried and packaged for later use.

[0077] In this embodiment, the particle size of the powder is less than 400 mesh, and the powder is subjected to the following additional treatments: refinement treatment by a ball mill to ensure the uniformity and reactivity of the powder; heat treatment in an inert gas atmosphere to remove adsorbed water and organic impurities on the surface of the powder; screening by a sieving machine to ensure the consistency and precise control of the powder particle size; adding an appropriate amount of surfactant to the powder to improve the dispersibility of the powder and prevent agglomeration; drying the treated powder in a drying oven to a moisture content of less than 0.5% to ensure the stability of the material and prevent hydrolysis. Experimental data show that the copper-free NaO material prepared according to the above steps S1 to S9 has excellent mechanical properties and wear resistance, does not contain heavy metals, and is environmentally friendly.

[0078] Experimental data: Synthesis method: Follow the above steps S1 to S9.

[0079] Reaction conditions: melting temperature 1500°C to 1600°C, melting time not less than 2 hours, ball milling time not less than 48 hours, ultrasonic treatment power 100W to 200W, cold isostatic pressing pressure 5 to 10 atmospheres, sintering temperature 1100°C to 1200°C, oil quenching temperature 150°C to 200°C, ultrasonic cleaning time 10 to 20 minutes.

[0080] Yield: The theoretical yield is 100%, and the actual yield exceeds 95%.

[0081] Purity: Through X-ray diffraction (XRD) analysis, the phase purity of copper-free NaO material reaches more than 99%.

[0082] Application and Effect: The copper-free NaO material is suitable for manufacturing high-performance friction materials, such as brake linings, etc. Experiments show that the copper-free NaO material prepared by this embodiment has excellent high-temperature stability and low wear rate, does not contain heavy metals such as copper, and is environmentally friendly.

[0083] Embodiment 10: A method for preparing a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 43.0 parts of sodium oxide, 3.0 parts of aluminum oxide, 5.0 parts of silicon oxide, 7.0 parts of calcium oxide, 6.0 parts of magnesium oxide, 9.0 parts of iron oxide, 5.2 parts of zinc oxide, 5.0 parts of titanium oxide, 6.0 parts of boride, 5.0 parts of barium oxide and 13.0 parts of water. The preparation method of this embodiment includes the following steps: S1. The aluminum oxide and silicon oxide are melted at 1590°C in a protective atmosphere for 3.5 hours to form a uniform melt, and then naturally cooled to 890°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for 96 hours, and the mass ratio of the ball-milling medium to the powder was 15:1. After the ball-milling, the powder was screened through a 400-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 was mixed with the powder obtained in step S2, deionized water was added, and the mixture was stirred at a speed of 1800 rpm for 3.5 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry was kept warm in a water bath at 58°C and ultrasonically treated with an ultrasonic processor at a power of 200 W for 60 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry was subjected to cold isostatic pressing at 10 atmospheres for 2 hours to form a dense green body; S6. The green body was sintered at 1190°C under nitrogen protection for 6 hours, and the green body was turned over every 30 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 170°C for 10 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 20 minutes to remove the remaining ground and polished materials on the surface, and then dried and packaged for later use.

[0084] In this embodiment, the particle size of the powder is less than 400 mesh, and the powder is subjected to the following additional treatments: refinement treatment by a ball mill to ensure the uniformity and reactivity of the powder; heat treatment in an inert gas atmosphere to remove adsorbed water and organic impurities on the surface of the powder; screening by a sieving machine to ensure the consistency and precise control of the powder particle size; adding an appropriate amount of surfactant to the powder to improve the dispersibility of the powder and prevent agglomeration; drying the treated powder in a drying oven to a moisture content of less than 0.5% to ensure the stability of the material and prevent hydrolysis. Experimental data show that the copper-free NaO material prepared according to the above steps S1 to S9 has excellent mechanical properties and wear resistance, does not contain heavy metals, and is environmentally friendly.

[0085] Experimental data: Synthesis method: Follow the above steps S1 to S9.

[0086] Reaction conditions: melting temperature 1590°C, melting time 3.5 hours, ball milling time 96 hours, ultrasonic treatment power 200W, cold isostatic pressing pressure 10 atmospheres, sintering temperature 1190°C, oil quenching temperature 170°C, ultrasonic cleaning time 20 minutes.

[0087] Yield: The theoretical yield is 100%, and the actual yield exceeds 96%.

[0088] Purity: Through X-ray diffraction (XRD) analysis, the phase purity of copper-free NaO material reaches more than 99%.

[0089] Application and Effect: The copper-free NaO material is suitable for manufacturing high-performance friction materials, such as brake linings, etc. Experiments show that the copper-free NaO material prepared by this embodiment has excellent high-temperature stability and low wear rate, does not contain heavy metals such as copper, and is environmentally friendly.

[0090] Comparative Example 1 This comparative example is a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 42.0 parts of sodium oxide, 2.5 parts of aluminum oxide, 4.5 parts of silicon oxide, 6.5 parts of calcium oxide, 5.5 parts of magnesium oxide, 8.5 parts of iron oxide, 4.5 parts of zinc oxide, 4.0 parts of titanium oxide, 5.0 parts of boride, 4.0 parts of barium oxide and 12.0 parts of water; The preparation method of the copper-free NaO material comprises the following steps: (a) melting aluminum oxide and silicon oxide in air at 1500° C. for 2 hours to form a melt, and then naturally cooling to 800° C. to obtain a prefabricated block; (b) grinding sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide in a ball mill with water as a medium for 24 hours, with a mass ratio of the ball milling medium to the powder being 5:1. After the ball milling, the powders were sieved through a 100-mesh sieve to obtain powders; (c) mixing the prefabricated block with the powder, adding deionized water, and stirring at 500 rpm for 1 hour using a low-speed mixer to form a slurry; (d) allowing the slurry to stand at room temperature, and then pouring it into a mold and drying it naturally to obtain a green body; (e) The green body is sintered in air at 1100° C. for 4 hours. After sintering, the green body is naturally cooled to obtain a copper-free NaO material.

[0091] Comparative Example 2 This comparative example is a copper-free NaO material, which is prepared from the following raw materials in parts by weight: 43.5 parts of sodium oxide, 3.5 parts of aluminum oxide, 5.5 parts of silicon oxide, 7.5 parts of calcium oxide, 6.5 parts of magnesium oxide, 9.5 parts of iron oxide, 5.5 parts of zinc oxide, 5.0 parts of titanium oxide, 6.5 parts of boride, 5.5 parts of barium oxide and 13.5 parts of water; The preparation method of the copper-free NaO material comprises the following steps: (a) melting aluminum oxide and silicon oxide in air at 1600° C. for 3 hours to form a melt, and then naturally cooling to 900° C. to obtain a prefabricated block; (b) ball milling sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide in a ball mill with water as a medium for 72 hours, with a mass ratio of ball milling medium to powder being 5:1. After the ball milling, the powders were sieved through a 100-mesh sieve to obtain powders; (c) mixing the prefabricated block with the powder, adding deionized water, and stirring at 500 rpm for 1 hour using a low-speed mixer to form a slurry; (d) allowing the slurry to stand at room temperature, and then pouring it into a mold and drying it naturally to obtain a green body; (e) The green body is sintered in air at 1200° C. for 5 hours. After sintering, the green body is naturally cooled to obtain a copper-free NaO material.

[0092] Experimental example The copper-free NaO materials prepared in Example 9 and Comparative Examples 1-2 were obtained respectively; The copper-free NaO material was used to perform performance tests, including mechanical properties, wear resistance and high temperature stability; wherein the copper-free NaO material of Example 9 was tested 3 times, the copper-free NaO material of Comparative Example 1 was tested 3 times, and the copper-free NaO material of Comparative Example 2 was tested 3 times; Test method: The mechanical properties, wear resistance and high temperature stability of copper-free NaO materials were tested using standard test methods; The test results are shown in Tables 1 to 3:

[0093] Table 1 Statistics of copper-free NaO material performance tests

[0094] Table 2 Microstructure analysis of copper-free NaO materials

[0095] Table 3 Environmental adaptability test of copper-free NaO materials From Tables 1 to 3, we can see that: The copper-free NaO material of Example 9 exhibits superior performance in performance tests, microstructure analysis, and environmental adaptability tests. Compared with Comparative Examples 1 and 2, the copper-free NaO material of Example 9 not only excels in mechanical properties, wear resistance, and high temperature stability, but also shows higher phase purity and particle size consistency, as well as lower porosity in the microstructure. In addition, the material of Example 9 also has better acid resistance, alkali resistance, heat resistance, and weather resistance, which enable the material to maintain stable performance under various environmental conditions and is suitable for a wider range of application scenarios. These test results verify the effectiveness of the technical solution of the present application in improving the performance of copper-free NaO materials.

[0096] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

[0097] The above descriptions are only some preferred embodiments of the present invention and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the embodiments of the present invention is not limited to the technical solutions formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features without departing from the above inventive concept. For example, the above features are replaced with (but not limited to) technical features with similar functions disclosed in the embodiments of the present invention.

Claims

1. A copper-free NaO material, characterized in that: The invention is prepared from the following raw materials in parts by weight: 42.2-43.0 parts of sodium oxide, 2.0-3.0 parts of aluminum oxide, 4.0-6.0 parts of silicon oxide, 6.4-7.0 parts of calcium oxide, 4.0-6.0 parts of magnesium oxide, 8.6-9.0 parts of iron oxide, 4.8-5.2 parts of zinc oxide, 4.0-5.0 parts of titanium oxide, 4.0-6.0 parts of boride, 4.0-5.0 parts of barium oxide and 12.3-13.0 parts of water.

2. The copper-free NaO material according to claim 1, characterized in that: It is made from the following raw materials in parts by weight: 42.2 parts of sodium oxide, 2.0 parts of aluminum oxide, 4.0 parts of silicon oxide, 6.4 parts of calcium oxide, 4.0 parts of magnesium oxide, 8.6 parts of iron oxide, 4.8 parts of zinc oxide, 4.0 parts of titanium oxide, 6.0 parts of boride, 4.0 parts of barium oxide and 12.3 parts of water.

3. The copper-free NaO material according to claim 1, characterized in that: It is made from the following raw materials in parts by weight: 43.0 parts of sodium oxide, 3.0 parts of aluminum oxide, 5.0 parts of silicon oxide, 7.0 parts of calcium oxide, 6.0 parts of magnesium oxide, 9.0 parts of iron oxide, 5.2 parts of zinc oxide, 5.0 parts of titanium oxide, 6.0 parts of boride, 5.0 parts of barium oxide and 13.0 parts of water.

4. The copper-free NaO material according to claim 1, characterized in that: It is made from the following raw materials in parts by weight: 42.8 parts of sodium oxide, 2.6 parts of aluminum oxide, 5.2 parts of silicon oxide, 6.8 parts of calcium oxide, 5.1 parts of magnesium oxide, 8.8 parts of iron oxide, 5.0 parts of zinc oxide, 4.5 parts of titanium oxide, 4.5 parts of boride, 4.5 parts of barium oxide and 13.0 parts of water.

5. The copper-free NaO material according to claim 1, characterized in that: The boride is a combination of one or more of borates, borax, boric acid, borosilicate, calcium borate and magnesium borate.

6. The copper-free NaO material according to claim 5, characterized in that: The boride is prepared by mixing borate, borax and boric acid, wherein the weights of the borate, borax and boric acid are equal.

7. The copper-free NaO material according to claim 5, characterized in that: The boride is borosilicate, and by weight, the silicon oxide comprises 4.0 parts and the boride comprises 6.0 parts.

8. The copper-free NaO material according to claim 5, characterized in that: The boride is calcium borate, and the purity of the calcium borate is greater than 99.5%.

9. A method for preparing the copper-free NaO material according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. The aluminum oxide and silicon oxide are melted at 1500°C to 1600°C in a protective atmosphere for at least 2 hours to form a uniform melt, and then naturally cooled to 800°C to 900°C to obtain a prefabricated block; S2. The sodium oxide, iron oxide, zinc oxide, titanium oxide and barium oxide were ball-milled in a ball mill with ethanol as the medium for at least 48 hours, and the mass ratio of the ball-milling medium to the powder was 10:

1. After the ball-milling, the powder was screened through a 200-mesh sieve to obtain a refined and uniform powder; S3. The prefabricated block obtained in step S1 is mixed with the powder obtained in step S2, deionized water is added, and the mixture is stirred at a speed of 1500 rpm for at least 2 hours using a high-speed stirrer to form a uniform slurry; S4. The slurry is kept in a water bath at 50°C to 60°C, and ultrasonically treated using an ultrasonic processor with a processing power of 100W to 200W for at least 30 minutes to further disperse the particles in the slurry; S5. The ultrasonically treated slurry is subjected to cold isostatic pressing at a pressure of 5 to 10 atmospheres for 1 to 2 hours to form a dense green body; S6. The green body is sintered at 1100°C to 1200°C under nitrogen protection for 4 to 6 hours, and the green body is turned over every 30 minutes during the sintering process to ensure uniform sintering; S7. After sintering, the green body is oil-quenched in hot oil at 150°C to 200°C for 5 to 10 minutes to reduce the residual stress inside the material; S8. The green body after oil quenching is naturally cooled at room temperature, and then the surface is ground and polished to obtain a smooth surface; S9. Finally, the ground and polished copper-free NaO material is ultrasonically cleaned in deionized water for 10 to 20 minutes to remove the grinding and polishing materials remaining on the surface, and then dried and packaged for later use.

10. The method for preparing the copper-free NaO material according to claim 1, characterized in that: In step S2, the particle size of the powder is less than 400 mesh, and the powder is subjected to the following additional treatments: a. Refinement treatment by ball mill to ensure the uniformity and reactivity of powder; b. Heat treatment in an inert gas atmosphere to remove adsorbed water and organic impurities on the powder surface; c. Screening by sieving machine to ensure the consistency and precise control of powder particle size; d. Add an appropriate amount of surfactant to the powder to improve the dispersibility of the powder and prevent agglomeration; e. Dry the treated powder in a drying oven until the moisture content is less than 0.5% to ensure the stability of the material and prevent hydrolysis.